The theory of evolution a history of controversy - Larson, Edward J. (Edward John); Burgstaller, Andreas; Teaching Company (Chantilly, Va. : Teaching Co., 2002)
Twelve lectures by Edward J. Larson on human evolution.
lecture 1. Before Darwin -- lecture 2. Evolution in the air -- lecture 3. Darwin's inspiration -- lecture 4. An intellectual revolution -- lecture 5. Debates over Mechanism -- lecture 6. Missing links -- lecture 7. Genetics enters the picture -- lecture 8. Social Darwinism and Eugenics -- lecture 9. America's Anti-Evolution crusade -- lecture 10. The Neo-Darwinian synthesis -- lecture 11. Scientific creationism -- lecture 12. Selfish genes and intelligent design.
Color recording system: NTSC.
Issued in container 25 x 17 x 3 cm.
Lecturer: Edward J. Larson.
DVD, region 1; Dolby digital.
Keywords: Evolution; Natural history